Prevalence, risk factors and course of osteoporosis in patients with Crohn’s disease at a tertiary referral center - Hoffmann, Peter; Krisam, Johannes; Kasperk, Christian; Gauss, Annika (Journal of Clinical Medicine, 2019)
Background: Patients with Crohn's disease are at increased risk for fractures due to low bone mineral density (BMD). Real-world data are necessary to optimize surveillance and treatment strategies. Methods: Patients with Crohn's disease who underwent at least one dual-energy X-ray absorptiometry (DXA) scans were recruited. The primary study endpoints were (1) prevalence of osteoporosis, and (2) factors influencing changes of BMD. To identify potential risk factors for reduced BMD, Mann-Whitney U-test was used for ordinal and continuous variables and x2-tests for categorical variables. Results with p < 0.05 were included in a multivariable analysis. To identify potential factors influencing changes in BMD, a generalized linear mixed model was applied. Results: 39.9% of the patients were diagnosed with normal BMD, 40.2% with osteopenia, and 19.8% with osteoporosis. The main risk factors for osteoporosis were low body mass index (BMI), previous bowel resections and male sex. The main risk factors for reduced BMD during further along the disease course were steroid use, history of immunomodulator treatment, female sex and decreased BMI. Conclusion: Low BMI, previous bowel resections and male sex were the main risk factors for the development of osteoporosis. Steroid use reduced BMD even under anti-inflammatory therapy, underlining that they should be used with great care in that patient group.
Gesehen am 12.02.2020